El Ganado Cracker de Florida - Jorge R. Rey (EDIS, 2010)
AN246, a 4-page illustrated fact sheet by Jorge R. Rey, is the Spanish language version of AN240: Florida Cracker Cattle. It describes this small to moderately-sized breed of cattle descended from the original cattle brought to Florida by the Spanish in the 1500s — history, breed characteristics, beef, organizations, and contacts. Published by the UF Department of Animal Sciences, July 2010.